The influence of natural convection on thermal properties of building enclosure with polystyrene boards/Putų polistireno plokštėmis izoliuotų pastatų sienų šiluminių savybių priklausomybė nuo natūralios konvekcijos - Samajauskas, Rolandas; Stankevičius, Vytautas (Journal of Civil Engineering and Management, 2000)
Building insulating materials with good insulation properties usually are porous, because they contain large amounts of air or other gas inside. The pore system can be closed, as in many cellular plastics, or open as in fibre materials. The mechanisms of heat transfer in porous material are: conduction in solid phase, radiation within material and conduction due to the gas confined in the insulation. In an open-pore material, like lightweight mineral wool, the transportation of heat can be further increased by air movement (convection) through the permeable material. Convection is impossible in a closed porous materials like polystyrene (EPS, XPS) boards. But heat losses can be increased by air movement if there are cracks between boards and other building envelope structures. The airflow velocity and direction may vary strongly due to the changing boundary condition. However, at the present time in Lithuania convection in insulating materials is considered as non-existent, when calculating heat transmission and designing building structures. Because of the lack of knowledge concerning air movement in external building structures, and how it is affecting the heat transfer, this investigation has been carried out. For research an equipment (Fig 2) was made, assigned for exploring both vertical and horizontal structures (height 2100 mm, width 1100 mm and thickness up to 300 mm). For reducing heat losses through the sides up to minimum, an equipment was built from slabs (thickness 150 mm). As the hot side of equipment gypsum board was applied to the surface of which 8 heat flow sensors and 9 thermocouples were attached. For maintaining constant and isothermal temperature of the surface of this partition (Θi, =+20°C), heating elements and ventilators were mounted inside the equipment. The cold surface of the equipment was of the same construction as the warm one only with the regulated slide valve with an area of 0,02 m2. It allows exploring the so-called not-ventilated structures. During the test, temperature was measured at different places and depths. The research was performed on the foam polystyrene plates of 3×50 mm of thickness with 3–5 mm air gaps. Measurements were conducted in the following sequence: 1. Two basic measurements of closed structure were performed for constant values of temperatures Θe=0°C and Θe=10°C. In this case the structure was held horizontally and heat flow was directed from top to bottom. Therefore it could be assumed that heat was transferred by conduction and radiation. 2. Measurements of the closed structure were performed on the equipment being in vertical position and for external temperature Θe=0°C and Θe=10°C. 3. Measurements of the opened structure. The measurement carried out for the same external environment conditions, the ventilating orifice being opened. The results of laboratory experiments allowed to assess the heat losses of the enclosure being arranged in the form of wall with air gaps applying foam polystyrene slabs. Different types of structures being investigated are shown in Fig 1. The Nu numbers for closed and ventilated structures are presented in Figs 8 and 9. The research results could be applied to enclosures with hard type insulation too. Although the natural convection does not occur inside the ideal material, but it takes place inside enclosure with air gaps. Thus, actual U-value depends on structural solutions and air tightness on building envelope. If wind barrier is permeable, then air filtration through the structure may cause even critical values for heat losses. Article in Lithuanian. First Published Online: 26 Jul 2012